2005
DOI: 10.1159/000084595
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy with Edrecolomab versus Observation in Stage II Colon Cancer: A Multicenter Randomized Phase III Study*

Abstract: iBackground: In a phase III study recruiting patients with stage II colon cancer the effect of adjuvant therapy with edrecolomab, a murine monoclonal antibody to the cell-surface glycoprotein 17-1A, was compared to observation alone. Patients and Methods: From January 1997 until July 2000 a total of 377 patients were postoperatively stratified according to tumor stage (T3 vs. T4) and center, and randomly allocated to either treatment with edrecolomab (cohort A, n = 183) or observation (cohort B, n = 194). Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 19 publications
0
36
0
1
Order By: Relevance
“…This well-tolerated murine IgG2a antibody, which was temporarily marketed in Germany, showed a significant increase in overall survival of colorectal cancer patients in the adjuvant setting in two out of four trials (Riethmüller et al, 1994(Riethmüller et al, , 1998Hempel et al, 2000;Punt et al, 2002;Hartung et al, 2005). The speaker concluded that despite a very benign safety profile of edrecolomab, its short half-life, rapid neutralisation by a mouse-anti-human antibody response, and a borderline clinical activity asks for development of an improved mAb, ideally of human nature.…”
Section: Epcam-directed Immunotherapies Under Developmentmentioning
confidence: 99%
“…This well-tolerated murine IgG2a antibody, which was temporarily marketed in Germany, showed a significant increase in overall survival of colorectal cancer patients in the adjuvant setting in two out of four trials (Riethmüller et al, 1994(Riethmüller et al, , 1998Hempel et al, 2000;Punt et al, 2002;Hartung et al, 2005). The speaker concluded that despite a very benign safety profile of edrecolomab, its short half-life, rapid neutralisation by a mouse-anti-human antibody response, and a borderline clinical activity asks for development of an improved mAb, ideally of human nature.…”
Section: Epcam-directed Immunotherapies Under Developmentmentioning
confidence: 99%
“…The first antibody used in passive immunotherapy was edrecolomab, a murine IgG2a antibody targeting Ep-CAM (Sears et al, 1984;Riethmuller et al, 1994). The therapeutic effect of this antibody administered alone or in combination with chemotherapy or GM-CSF (Mellstedt et al, 2000) was not conclusive, but it showed a very benign safety profile (Fields et al, 2002;Punt et al, 2002;Hartung et al, 2005). To reduce immunogenicity and enhance antibodydependant cytotoxicity, complement dependant cytotoxicity and serum half-life, humanised antibodies ING-1 (de Bono et al, 2004), 3622W94 (Abdullah et al, 1999;Martin et al, 1999) and fully human IgG1 antibody MT201 (adecatumumab) (Naundorf et al, 2002;Brischwein et al, 2005) were developed.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical testing showed the chimeric construct increased mononuclear cell-mediated ADCC and prolonged half-life than the murine mAb. In addition, it develops no human anti-mouse antibodies (Hartung et al, 2005).…”
Section: Targets In Solid Tumorsmentioning
confidence: 99%